The Use of Fiber-Reinforced Scaffolds Cocultured with Schwann Cells and Vascular Endothelial Cells to Repair Rabbit Sciatic Nerve Defect with Vascularization - Gao, Hongyang (Hindawi Publishing Corporation, 2013)
To explore the feasibility of biodegradable fiber-reinforced 3D scaffolds with satisfactory mechanical properties for the repair of long-distance sciatic nerve defect in rabbits and effects of vascularized graft in early stage on the recovery of neurological function, Schwann cells and vascular endothelial cells were cocultured in the fiber-reinforced 3D scaffolds. Experiment group which used prevascularized nerve complex for the repair of sciatic nerve defect and control group which only cultured with Schwann cells were set. The animals in both groups underwent electromyography to show the status of the neurological function recovery at 4, 8, and 16 weeks after the surgery. Sciatic nerve regeneration and myelination were observed under the light microscope and electron microscope. Myelin sheath thickness, axonal diameter, and number of myelinated nerve fiber were quantitatively analyzed using image analysis system. The recovery of foot ulcer, the velocity of nerve conduction, the number of regenerating nerve fiber, and the recovery of ultrastructure were increased in the experimental group than those in the control group. Prevascularized tissue engineered fiber-reinforced 3D scaffolds for the repair of sciatic nerve defects in rabbits can effectively promote the recovery of neurological function.